Peningkatan Pemahaman Mahasiswa dalam Mata Kuliah Statistika Melalui Metode Pemberian Tugas Terstruktur - Dewi Devita; Deby Erdiani (Universitas Putra Indonesia YPTK Padang, 2019)
This study was committed at the college education department of information management classes. As for the purpose of this study is to improve students’ understanding of statistics through the method of structured instruction in college design targeted study paths based on the resulting data to bolster student’s understanding in the areas where they need to improve the most. This study class action research of consists 3 cycle. The subjek of this study is an informatika management student. Data collection techniques through test results. In this study, the three cycle are 41 %, the result of cycle II has reached 66 % expected. The observation on the cycle of III indicate that the students’ activity has reached 83% to the expected level. Based on this study indicates that the method of structured tasks can have a positive effect on student’s studying.